海 运述 评 2018年 - United Nations Conference on Trade; Development (United Nations, 2019)
The Review of Maritime Transport is an UNCTAD flagship publication, published annually since 1968. Around 80 per cent of the volume of international trade in goods is carried by sea, and the percentage is even higher for most developing countries. The Review of Maritime Transport provides an analysis of structural and cyclical changes affecting seaborne trade, ports and shipping, as well as an extensive collection of statistical information.